2019
DOI: 10.31224/osf.io/bvhzc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation and thermodynamic analysis of the porous functionally graded bolted joint

Abstract: Ceramic-metal functionally graded materials (FGMs) have been extensively used in aerospace engineering where high strength and excellent heat insulation materials are desired. In this paper, the thermodynamic behavior of the Thermal Protection System (TPS) used bolted joints made up of porous ZrO2/(ZrO2+Ni) FGMs is investigated by finite-element (FE) modeling. The bolted joint is subjected to reentry heating corresponding to the Access to Space Vehicle. Thermodynamic simulations are carried out to yield the tr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…36,37 Also, it is found by researchers that porosity can greatly affect the thermal conductivity, which has been deliberately utilized to design thermal resistance of ceramics. [38][39][40] Researchers have fabricated Si 3 N 4 ceramic materials using different additives, and it is confirmed that the function of different sintering aids is different in the preparation of Si 3 N 4 ceramics. For instance, to improve thermal conductivity, rare earth oxides like Y 2 O 3 and Yb 2 O 3 can be chosen as sintering aids.…”
Section: Materials and Methodologymentioning
confidence: 92%
“…36,37 Also, it is found by researchers that porosity can greatly affect the thermal conductivity, which has been deliberately utilized to design thermal resistance of ceramics. [38][39][40] Researchers have fabricated Si 3 N 4 ceramic materials using different additives, and it is confirmed that the function of different sintering aids is different in the preparation of Si 3 N 4 ceramics. For instance, to improve thermal conductivity, rare earth oxides like Y 2 O 3 and Yb 2 O 3 can be chosen as sintering aids.…”
Section: Materials and Methodologymentioning
confidence: 92%